UWB Localization System for Indoor Applications: Concept, Realization and Analysis. (28th May 2012) - Zwirello, Lukasz; Schipper, Tom; Harter, Marlene; Zwick, Thomas
Abstract : A complete impulse-based ultrawideband localization demonstrator for indoor applications is presented. The positioning method, along with the method of positioning error predicting, based on scenario geometry, is described. The hardware setup, including UWB transceiver and time measurement module, as well as the working principles is explained. The system simulation, used as a benchmark for the quality assessment of the performed measurements, is presented. Finally, the measurement results are discussed. The precise analysis of potential error sources in the system is conducted, based on both simulations and measurement. Furthermore, the methods, how to improve the average accuracy of 9 cm by including the influences of antennas and signal-detection threshold level, are made. The localization accuracy, resulting from those corrections, is 2.5 cm.